KENDALI SAKELAR EMPAT ANTENNA BERSUSUN UNTUK PENJEJAKAN INTERFERENCE FREKUENSI TTC SATELIT LAPAN (SWITCH CONTROL SYSTEM FOR FOUR ARRAY ANTENNA FOR TRACKING OF LAPAN’S SATELLITE TTC INTERFERENCE FREQUENCY) - Arif Hidayat; Wahyudi Hasbi; Elyas Palantei; Syafruddin Syarif (National Institute of Aeronautics and Space - LAPAN, 2017)
Telemetry Tracking and Command (TTC) of LAPAN’s satellite use UHF frequency. This frequency is susceptible to interference by an amateur radio transmitter. One method to look for an interference transmitter is Doppler Effect. To get the optimal value of the Doppler shift frequency, it is necessary to have stabilized antenna switch as controller of antenna array. The RF switches controlled by an Arduino board produced 500 Hz Doppler frequency. Other hardwares are Demodulator, clock Arduino Board, and Universal Serial Bus (USB) soundcard as the input for the searching software. The results can be shown using the open access sound Doppler. The system has been able to detect UHF transmitters and repeaters received by the device. For upgrade, the data processing system can be done using Matlab software to easier process and analysis. AbstrakTelemetry Tracking And Command (TTC) satelit LAPAN menggunakan frekuensi UHF. Frekuensi UHF rentan terhadap interference. Salah satu metode mencari pemancar interference menggunakan metode efek Doppler. Untuk mendapat nilai pergeseran frekuensi sesuai efek Doppler yang dibutuhkan, diperlukan sakelar antena yang stabil, yang berfungsi sebagai pengontrol antena array. Rangkaian sakelar RF di kontrol dengan Arduino board menghasilkan Doppler frekuensi 500 Hz. Demodulator, clock Arduino Board dan Soundcard sebagai input software pencari. Hasil outputnya dapat dilihat dengan menggunakan software open akses sounDoppler. Sistem ini mampu mendeteksi pemancar maupun repeater yang diterima oleh perangkat. Upgrade sistem dari penelitian ini adalah proses pengolahan data dapat dilakukan secara mandiri menggunakan software Matlab sehingga lebih mudah untuk diolah dan dianalisis.